Effect of Dynamic Center Region on the Flow and Mixing Efficiency in a New Tri-Screw Extruder Using 3D Finite Element Modeling - X. Z. Zhu; Y. D. He; G. Wang (International Journal of Rotating Machinery)
Three-dimensional finite element modeling of polymer melt flowing in a new co-rotating tri-screw extruder was established with mesh superposition technique. Based on the particle tracking technology, three typical particle trajectories in the tri-screw extruder were calculated using a 4th-order-Runge-Kutta method to study the dynamic motions of the particles. Then the flow visualizations in the local center region were carried out. Moreover, the dispersive, distributive and stretching mixing efficiencies of the tri-screw and twin-screw extruders were compared, respectively. The results show that when the particles move from one screw to another, there are great abrupt changes in the velocities and displacements, which induce the abrupt change in the stress magnitude. Most of particles, which are initially distributed in the inlet plane of the center region, fast flow out the outlet and don’t pass through any screw. This special phenomenon induces a series of new characteristics in the residence time distribution (RTD), flow number, segregation scale and time averaged efficiency. In comparison with the twin-screw extruder, the tri-screw extruder has better mixing efficiency.